Book Review Sholahudin, Umar. (2024). Konflik Agraria: Kebijakan Industrialisasi, Dualisme Hukum, dan Dekade Krisis. Intrans Publishing. 182 pp. - Sair, Abdus (Universitas Wijaya Kusuma Surabaya, 2025)
The book Konflik Agraria: Kebijakan Industrialisasi, Dualisme Hukum, dan Dekade Krisis offers a critical reflection on the imbalance in the management of agrarian resources in Indonesia. It thematically discusses issues of agrarian reform, the historical roots of conflict, sociological-legal approaches, and case studies such as Banyuwangi, which illustrate how industrialization policies have escalated land conflicts. The author highlights the dominance of state and corporate power in shaping policies, along with the weak legal protection afforded to agrarian communities. While the book presents important data and case studies, it is considered lacking in theoretical depth, field-based approaches, and transformative solutions. Additional criticism is directed at its disjointed narrative structure and less evocative language. Despite these limitations, the book serves as a valuable starting point for understanding agrarian conflict, though it leaves ample room for deeper conceptual exploration and approaches more aligned with social justice.Keywords: agrarian conflict, industrialization, agrarian law, agrarian reform, social justice.